NAV Portugal's performance within the single European Sky Initiative - Coelho, Ana Beatriz Trindade (2018)
NAV Portugal is the Air Navigation Service Provider in Portugal, providing air traffic control services in the airspace under the country’s responsibility. Recently, the company has been included in an initiative launched by the European Commission, called the Single European Sky. This aims for a unification of the European airspace, improving it in four main pillars: safety, capacity, environment, and cost-efficiency. To each of them, Key Performance Indicators need to be computed and monitored, all having pre-defined targets. The presented work project will be analyzing how NAV Portugal is doing in the pillar of capacity, proving suggestions if needed.